1997
DOI: 10.1038/bjc.1997.514
|View full text |Cite
|
Sign up to set email alerts
|

Primary systemic therapy for operable breast cancer - 10-year survival data after chemotherapy and hormone therapy

Abstract: Summary Between 1984 and 1990, 94 women presenting to the Edinburgh Breast Unit with operable breast cancer of 4 cm or greater in diameter (T2, T3, NO, Ni, MO) were given preoperative systemic therapy. Initially, all women received hormone therapy, with CHOP (cyclophosphamide 1 g m-2, doxorubicin 50 mg m-2, vincristine 1.4 mg m-2 to a maximum of 2 mg and prednisolone 40 mg per day orally for 5 days) chemotherapy being administered to those who failed to respond by 3 months. After April 1987, first-line hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 25 publications
3
33
0
1
Order By: Relevance
“…Among the most useful of these are the presence and number of axillary lymph-node metastasis, tumour size, histological type and SBR grade. The most powerful is indisputably the node involvement with a prognosis inversely related to the number of involved nodes, even after neoadjuvant chemotherapy and whatever the treatment administered (Cameron et al, 1997;Pierga et al, 2000;Cure et al, 2002). SBR grading is also by itself a prognostic parameter; survival was worse in patients with poorly differentiated tumours (grades II and III) compared with well-differentiated grade I tumours (Simpson et al, 2000;Latinovic et al, 2001;Amat et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most useful of these are the presence and number of axillary lymph-node metastasis, tumour size, histological type and SBR grade. The most powerful is indisputably the node involvement with a prognosis inversely related to the number of involved nodes, even after neoadjuvant chemotherapy and whatever the treatment administered (Cameron et al, 1997;Pierga et al, 2000;Cure et al, 2002). SBR grading is also by itself a prognostic parameter; survival was worse in patients with poorly differentiated tumours (grades II and III) compared with well-differentiated grade I tumours (Simpson et al, 2000;Latinovic et al, 2001;Amat et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The PST in general do not offer a survival advantage over standard adjuvant treatment, but may identify patients with a pathologically confirmed complete response (45,46). This clinical response to PST is associated with improved survival (50,54,55) and reflects a great benefit to ϳ14% of the PST-treated patients. Studies elaborating PST have demonstrated that early gene expression changes are significantly associated with clinical response (56,57).…”
Section: Introductionmentioning
confidence: 90%
“…13 Several phase 2 studies have demonstrated the feasibility of various endocrine treatments in elderly breast cancer patients with advanced locoregional disease, thus suggesting an alternative approach to initial surgery. 14,15 Choice of patients for this strategy follows from well-established predictive and prognostic variables for response to endocrine therapy in more advanced disease, specifically the presence of ER and PgR, advanced age, and welldifferentiated tumors. Most studies have reported lower objective response and pCR rates (50%-70% and <5%-10%, respectively) than have been reported for primary chemotherapy, and the time spent on endocrine therapy required to halve the tumor volume is often longer than that with chemotherapeutic agents (>3 months).…”
mentioning
confidence: 99%